Security of 5G Network Slicing: Identifying Vulnerabilities in The Virtualization of Mobile Network (International Journal of Scientific Research in Science and Technology, 2026)
5G network slicing is currently an important element of modern mobile networks’ architecture. It lets many virtualised logical networks operate on the same physical infrastructure. This model supports a wide range of service requirements, consisting of enhanced Mobile Broadband (eMBB), Ultra-Reliable Low-Latency Communications (URLLC), and massive Machine-Type Communications (mMTC). It provides this by employing Software-Defined Networking (SDN), Network Function Virtualisation (NFV), cloud/edge computing, and programmable orchestration. Even though virtualisation has these advantages, it also presents serious security issues through creating the attack surface greater and placing slices at risk because of vulnerable isolation, insecure orchestration, authentication failures, shared-resource exploitation, and inter-slice attacks. This study investigates the main vulnerabilities influencing the security of 5G network slicing using a qualitative literature review of existing research. The investigation shows that vulnerabilities in SDN/NFV-enabled environments may threaten confidentiality, integrity, and availability over the entire slice lifecycle. The research suggests that traditional static security measures are not sufficient for highly dynamic and multi-tenant 5G ecosystems. Accordingly, to protect a system effectively, it requires security frameworks that are properly integrated, adaptable, and cross-layered. These should include strong slice isolation, secure management and orchestration, continuous monitoring, and smart defense mechanisms.